Mycetophila evanida Lastovka 1972 ... - Polevoi, A. V.; Maximova, Yu. V.; Subbotina, E. Yu. (Zenodo, 2020)
Mycetophila evanida Laštovka, 1972 MATERIAL. 1 ♂, Tareya, 2– 7.08.2010, (FRIP); 1 ♂, Lemberov, 19.07.2012 (ISEA). DISTRIBUTION. Holarctic: Greenland [Söli et al., 2015], Europe and Mongolia [Laštovka, 1972; Jurgenstern et al., 2015]. In Russia was recorded from Karelia [Zaitzev, 2003]. ... : Published as part of Polevoi, A. V., Maximova, Yu. V. & Subbotina, E. Yu., 2020, New data on the fungus gnats (Diptera: Bolitophilidae, Keroplatidae, Mycetophilidae) of the Taimyr Peninsula with a description of two new species of the genus Boletina Staeger, pp. 315-326 in Russian Entomological Journal 29 (3) on page 320, DOI: 10.15298/rusentj.29.3.13, http://zenodo.org/record/13165149 ...